The impact of morning versus afternoon exercise on iron absorption in athletes - McCormick, R.; Moretti, D.; McKay, A. K. A.; Laarakkers, C. M.; Vanswelm, R.; Trinder, D.; Cox, G. R.; Zimmerman, M. B.; Sim, M.; Goodman, C.; Dawson, B.; Peeling, P. (Medicine & Science in Sports & Exercise, 2019)
Purpose This study examined postexercise inflammatory, hepcidin, and iron absorption responses to endurance exercise performed in the morning versus the afternoon.